1998
DOI: 10.1080/10587259808024385
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrol of Smectic Spacing

Abstract: We report on the results of optical, X-ray and NMR studies of light-induced phenomena in smectic phases triggered by molecular phototransformations.UV irradiation causes trans-to-cis isomerization of the dopant molecules while irradiation in thc visible part of the spectrum facilitates cis-to-trans relaxation. Cis-to-trans isomerization decreaws the smectic layers' spacing; as the result, a smectic slab undergoes an undulation instability and/or formation of focal conic domains. These textures arc nonuniform a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…By photo-addressing the sample and changing the trans-to-cis ratio, one can drive the azobenzene molecules into and out of the smectic layers 116,117 . Relocation of the molecules changes the smectic layer spacing 118 which in its turn causes mechanical instabilities such as Helfrich-Hurault undulations of layers 119 .…”
Section: Static Distortionsmentioning
confidence: 99%
See 1 more Smart Citation
“…By photo-addressing the sample and changing the trans-to-cis ratio, one can drive the azobenzene molecules into and out of the smectic layers 116,117 . Relocation of the molecules changes the smectic layer spacing 118 which in its turn causes mechanical instabilities such as Helfrich-Hurault undulations of layers 119 .…”
Section: Static Distortionsmentioning
confidence: 99%
“…116,117 Relocation of the molecules changes the smectic layer spacing 118 which in its turn causes mechanical instabilities such as Helfrich-Hurault undulations of layers. 119 Recent studies of molecular transport in smectic LCs revealed a number of interesting features. Experimental and numerical studies of lyotropic smectics formed by long rigid rods (such as lamentous fd virus) demonstrated a hopping transport: 120,121 the rods jump from one layer to another without signicant reorientation.…”
Section: Static Distortionsmentioning
confidence: 99%
“…One might notice in Figure 4b that the iteration process of filling the gaps between the large circles with the smaller one interrupts at a certain macroscopic scale, and domains smaller than about 2–3 μm in size do not form. The explanation of this cut‐off in the iterative filling is given by Folks et al:39…”
Section: Periodic Array Of Fcdsmentioning
confidence: 99%
“…An important interplay between light and the structure of liquid crystals was first observed by Folks et al (18) and has been excellently explained by simulation studies (19) invoking the concept of photo-driven nanophase segregation in smectic liquid crystals. This concept was extended by us to explain the experimental observation of a photo-induced disorder-to-order transition (20), and induction of a layered mesophase in the presence of photo-irradiation (21,22); these observations are outlined below.…”
Section: Dynamic Self-assembly Of the Smectic Phasementioning
confidence: 97%